Analisis Kontrastif Verba Bahasa Jawa dan Bahasa Arab Berdasarkan Keterangan Waktu - Azizi, M. Riza; Sukarno (Universitas KH. Mukhtar Syafaat, 2024)
Each language has its own characteristics and characteristics and peculiarities from other languages. This study aims to describe the differences in the structure of Javanese and Arabic verbs from the adverb aspect of time. The method used in this research is descriptive contrastive. The data of this research are verbs based on time information in Javanese and Arabic. The data sources for this research are textbooks and everyday conversations that are often used in Javanese. Data collection techniques in this study used observing techniques and note-taking techniques. The data analysis technique was carried out using the agih method, namely choosing and determining verbs in Javanese and Arabic, then describing their differences based on time information in terms of structure and morphological changes. The results of the study show differences in the forms of verbs in Javanese and Arabic based on adverbs of time. These differences are viewed in terms of structure and morphological changes in the verbs of the two languages. In Javanese, verbs have additional adverbs of time, namely wes (had), ijek (still), and arep (will), but in Arabic the adverbs of time have merged with these verbs. In Javanese the verb does not change even though the adverb of time changes, whereas in Arabic the writing changes according to the verb that accompanies it.